Filtro digital híbrido para sistemas embarcados de alta potência - Martini, Guilherme Henrique Kaehler (2013)
This work presents the project, implementation and evaluation of a hybrid filter used for noise supressing in high power switching converters. It is optimized to reduce impulsive noise that is commonly present in high power devices like frequency inverters that control three-phase motors. The hybrid filter is evaluated empirically in a frequency inverter that is controlled by an embedded system. This approach is compared to classical ones, like the moving average, the finite impulse response (FIR) and the infinite impulse response (IIR) filters.